One-Step Hydrothermal Synthesis of Cu2ZnSnS4 Nanoparticles as an Efficient Visible Light Photocatalyst for the Degradation of Congo Red Azo Dye - Henríquez, Rodrigo; Salazar Nogales, Paula; Grez Moreno, Paula; Muñoz Cartagena, Eduardo; Leyton Bongiorno, Patricio; Navarrete-Astorga, Elena; Dalchiele, Enrique A. (MDPI, 2023)
A hydrothermal method was successfully employed to synthesize kesterite Cu2ZnSnS4 (CZTS) nanoparticles. X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), and optical ultraviolet-visible (UV-vis) spectroscopy were used for characterization of structural, chemical, morphological, and optical properties. XRD results confirmed that a nanocrystalline CZTS phase corresponding to the kesterite structure was formed. Raman analysis confirmed the existence of single pure phase CZTS. XPS results revealed the oxidation states as Cu+, Zn2+, Sn4+, and S2−. FESEM and TEM micrograph images revealed the presence of nanoparticles with average sizes between 7 nm to 60 nm. The synthesized CZTS nanoparticles bandgap was found to be 1.5 eV which is optimal for solar photocatalytic degradation applications. The properties as a semiconductor material were evaluated through the Mott–Schottky analysis. The photocatalytic activity of CZTS has been investigated through photodegradation of Congo red azo dye solution under solar simulation light irradiation, proving to be an excellent photo-catalyst for CR where 90.2% degradation could be achieved in just 60 min. Furthermore, the prepared CZTS was reusable and can be repeatedly used to remove Congo red dye from aqueous solutions.
Keywords: Fotocatálisis; Sulfuros minerales; CZTS; Congo red azo dye; Hydrothermal; Photocatalysis